MODEL PENGUKURAN KINERJA DAN EFISIENSI SEKTOR PUBLIK DENGAN METODE FREE DISPOSABLE HULL (FDH) - Kurnia, Akhmad Syakir (JURNAL BISNIS STRATEGI, 2006)
Improved efficiency is the main effect expected from fiscal decentralization. It could be gained on the presumptions that local governments are much better in identifying and fulfilling local public preferences, since they are closer to them, and in mobilizing and using local resources to pay for goods and services having purely local impacts. Once improved efficiency could be gained, public sector performance increase. I developed a model to measure public sector efficiency (PSE) and public sector performance (PSP). I compute public sector performance (PSP) and Public Sector Effociency (PSE) indicators comprising a composite consists of five sub-indicators. The first two indicators reflects socio-economic indicators that take into account education and health outcomes. Three other indicators reflect the standard "musgravian" task for government: a/location, distribution and stabilisation. Then, the model is applied to measure public sector performance and efficiency of Kabupaten/Kota in Central Java Province.